Sistema de avaliação e tratamento da coluna lombar com o uso de tração mecânica - Carvalho, André Sólon de [UNESP] (2015)
According to World Health Organization (WHO), disorders of the spine affect about 85% of world population at some stage in their life, being the second leading cause of work disability in adulthood. A herniated lumbar disc is one of the most common diseases in clinical practice by neurosurgeons and orthopedic surgeons, however, the treatment, contrary to what many believe is the conservative principle, surgery is indicated only in patients with symptoms refractory to treatment with physiotherapy and osteopathy, as is common for the patient does not recover quickly, and up to 38% of patients may need more surgery. The pull back is a powerful tool to reposition the joint and release of nerve compression, thus avoiding a large number of cases, surgery. For this it developed in this work a stretcher capable of performing lumbar traction, with three innovations: first, the use of an electro (FES) for the correct placement of electrodes surface electromyography (EMG) factor that minimizes the error in data collection. The second is the positioning of the patient in a supine position, a factor that favors the draw, because the anatomy of the lumbar spine. The third, dynamic traction, table has the ability to perform traction during flexion-extension movement. To assess the efficiency of the system were evaluated ten (10) volunteers, data angle, and magnitude of applied force or load ideal, time and frequency drift. The conclusion of this study was a better use of the benefits of lumbar traction and it is believed that the values generated serve as a scientific contribution to aid in the treatment of pathologies of the lumbar spine